E-commerce and value chain in grape exporting companies - Vilela-Guerrero, Claudia (2024)
The evolution of electronic commerce has been crucial to improving the value chain in the agricultural sector.After the pandemic, the importance of digital tools in all economic sectors was highlighted.The restrictions imposed to contain the spread of the disease led to the digitalization of the economy, with digital commerce being a key element for companies.This research focuses on determining the relationship between electronic commerce and the value chain in grape exporting companies.The proposed hypothesis suggests a positive relationship between both variables.To validate it, a questionnaire was applied as a data collection instrument, aimed at collaborators of the companies selected in the study.The results indicated that the hypothesis was validated, although the relationship was positive, but not significant.This reflects that, although the marketing of grapes is being carried out digitally, this is not the main means.The links in the value chain have not yet been fully digitized or mechanized.If these tools are implemented on a larger scale, the value chain could be improved and export growth boosted.However, there is still a way to go to achieve complete digitalization of the sector.